An update on ABO‐incompatible kidney transplantation. (24th November 2014) - Zschiedrich, Stefan; Kramer‐Zucker, Albrecht; Jänigen, Bernd; Seidl, Maximilian; Emmerich, Florian; Pisarski, Przemyslaw; Huber, Tobias B.
Summary: ABO‐incompatible kidney transplantation is nowadays a well‐established procedure to expand living donor transplantation to blood group incompatible donor/recipient constellations. In the last two decades, transplantation protocols evolved to more specific isohaemagglutinin elimination techniques and established competent antirejection protection protocols without the need of splenectomy. ABOi kidney transplantation associated accommodation despite isohaemagglutinin reappearance, C4d positivity of peritubular capillaries as well as the increased incidence of bleeding complications is currently under intense investigation. However, most recent data show excellent graft survival rates equivalent to ABO‐compatible kidney transplantation outcome.